(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Soleha S, Muslim A, Suwandi S, Kadir S, Pratama R. 2021. Host range studies of Fusarium oxysporum, causal agent of seedling wilt disease of Acacia mangium. Biodiversitas 23: 25-32. Fusarium oxysporum is a serious pathogen that causes severe wilt disease in commercial nurseries of Acacia mangium in South Sumatra, Indonesia. This study aimed to investigate the host range of F. oxysporum as a nursery wilt pathogen in A. mangium and several forest and industrial plants. Three isolates of F. oxysporum with different translation elongation factor (tef 1-a) sequences were tested for pathogenicity on different fabaceae family plants and the growth of population was also observed. The results showed that all the three isolates were able to infect all the tested plants with different reactions of wilt disease. The Acacia crassicarpa and Falcataria moluccana were highly susceptible; Archidendron pauciflorum, Leucaena leucocephala, and Parkia speciosa were moderately vulnerable and Acacia auriculiformis was moderately resistant. The pathogen population in A. crassicarpa and F. moluccana grew rapidly along with the increase in disease scores, while in L. leucocephala it was moderate, and slow in A. pauciflorum, P. speciosa and A. auriculiformis plants. In conclusion, F. oxysporum pathogen, which was isolated from A. mangium, has a wide range of hosts in the fabaceae family.